Analisis Judul Lagu “Sebelah Mata” Karya Band Efek Rumah Kaca Menggunakan Pendekatan Semiotika - Annisa Herayani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
Analysis of the title of the song "One Eye" by the band The Greenhouse Effect is backgrounded by the rapid development of this music among teenagers, therefore it aims to analyze the title of the song "Next to the Eye" by the Greenhouse Effect band using a semiotic approach and hermeutic reading to understand the meaning implied in the fragments of the lyrics. The method used is descriptive qualitative. The result of this study was that the form of signifier and sginified was found in the version of the song with a certain meaning. The lyrics of this song "One Eye" by ERK use a very good selection of language, not easy enough to capture the meaning but the lyrics contained can be directly touching when read.